2001
DOI: 10.1074/jbc.m008847200
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Proximal ERK Signaling Is Required for M-calpain Activation Downstream of Epidermal Growth Factor Receptor Signaling

Abstract: Localization of signaling is critical in directing cellular outcomes, especially in pleiotropic signaling pathways. The extracellular signal-regulated kinase (ERK)/ microtubule-associated protein kinase, which promotes cell migration, proliferation, and differentiation is found in the nucleus and throughout the cytoplasm. Recently, it has been shown that nuclear translocation of ERK is required for transcriptional changes and cell proliferation. However, the cellular consequences, of cytoplasmic signaling have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
167
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(177 citation statements)
references
References 41 publications
9
167
1
Order By: Relevance
“…However, ERKs extranuclear component is just as important. It has been estimated that half of the ERKs content remains in the cytoplasm after stimulation [62] and processes such as the formation of cell-matrix contacts, [63] adhesion, [64] endosomal traffic, [65] Golgi fragmentation, [66] and anti-apoptotic signaling [67] are dependent on ERK extranuclear activity. It fact, nearly half of the $180 proteins thus far identified as ERKs substrates, are non-nuclear proteins.…”
Section: Some Space For Erksmentioning
confidence: 99%
“…However, ERKs extranuclear component is just as important. It has been estimated that half of the ERKs content remains in the cytoplasm after stimulation [62] and processes such as the formation of cell-matrix contacts, [63] adhesion, [64] endosomal traffic, [65] Golgi fragmentation, [66] and anti-apoptotic signaling [67] are dependent on ERK extranuclear activity. It fact, nearly half of the $180 proteins thus far identified as ERKs substrates, are non-nuclear proteins.…”
Section: Some Space For Erksmentioning
confidence: 99%
“…Calpain cleavage of talin here is a rate limiting step in disassembly of other focal adhesion components including zyxin, paxillin and vinculin [190]. Recent studies have demonstrated that growth factor stimulation of calpain activity and cellular deadhesion is dependent upon ERK [191,192]. Calpain is directly phosphorylated by ERK in response to EGF stimulation and this increases calpain's proteolytic activity [96].…”
Section: Regulation Of Focal Adhesions and Actin By Proteolysismentioning
confidence: 99%
“…Together, these data suggest that calcium and growth-factormediated phosphorylation can independently activate calpains in an isoform-specific fashion. Interestingly, only membraneproximal calpain 2 is activated by ERK-mediated phosphorylation (Glading et al, 2001), which suggests that there are alternative modes of activation for certain calpain 2 subpopulations.…”
Section: Fig 2 (A)mentioning
confidence: 99%